Asperger Syndrome and Autism Compared - J Gordon Millichap (Pediatric Neurology Briefs, 1995)
The validity and neuropsychological characterization of Asperger syndrome (AS) was investigated by comparison with Higher-Functioning Autism (HFA) (ie autism associated with overall normal intelligence) in 73 potential subjects recruited from a consecutive case series seen at the Developmental Disabilities Clinic, Child Study Center, Yale University School of Medicine, New Haven, CT.